2021
DOI: 10.1017/s136898002100166x
|View full text |Cite
|
Sign up to set email alerts
|

Iron status in late pregnancy is inversely associated with birth weight in Colombia

Abstract: OBJECTIVE: Gestational Anaemia (GA) is common in developing countries. This study assessed the relationship of late GA and negative perinatal outcomes in participants recruited in a reference maternity unit of the Caribbean region of Colombia. DESIGN: Prospective analytical birth cohort study. Maternal haemoglobin and serum ferritin (SF) levels were measured. GA was defined as haemoglobin levels <11 g/dL, SF depletion as SF levels <12 ng/mL. Birth outcomes such as low birth weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
3
6
0
Order By: Relevance
“…Finally, maternal anaemia had significant effects of on the newborn birth weight. This study’s findings are similar to those study reported in China 61 , India 40 , Brazil 62 , Nepal 63 Colombia 64 , Eastern Ethiopia 65 , and Southern Punjab, Asia 66 . This could be because of intrauterine growth restriction.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, maternal anaemia had significant effects of on the newborn birth weight. This study’s findings are similar to those study reported in China 61 , India 40 , Brazil 62 , Nepal 63 Colombia 64 , Eastern Ethiopia 65 , and Southern Punjab, Asia 66 . This could be because of intrauterine growth restriction.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the absence of effective hygienic measures (i.e., correct sanitary handling of stools) favor the transmission of the infection and the economic constraints of the affected countries contribute to the problem. Only three studies in Latin America have evaluated the impact of these infections in pregnancy [7,41,50]. Two of them showed a high prevalence of helminth infection during pregnancy and its association with GA. Interestingly, despite having data about the impact of intestinal helminthiasis in pre-kinder population from the National Survey of Parasitism, there is no data regarding the prevalence of this infection in the gestational age in Colombia [60].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, prenatal iron supplementation is routinely recommended worldwide to prevent iron deficiency anemia ( 3 ). At the same time, studies show that excess iron may increase the risk of low birth weight ( 4 ), preterm births ( 5 ), and especially, hypertensive disorders in pregnancy ( 6 ). Therefore, most studies support lowering the dose of supplemented iron during pregnancy ( 7 ).…”
Section: Introductionmentioning
confidence: 99%